Perlindungan Hukum terhadap Korban Tindak Pidana Kekerasan dalam Rumah Tangga (KDRT) - Albi Ternando; Naning Ridia; Wawan Putra Hs; Riko Prasetyo; Emir Adzan Syazali (Wajah Hukum, 2026)
Domestic violence requires the role of the state through strong legal regulations to provide optimal protection for victims. This study examines legal regulations related to the crime of domestic violence and efforts to protect victims. The method used is normative legal research with a library approach through a review of relevant laws and legal literature, such as the Criminal Code (KUHP), the Criminal Procedure Code (KUHAP), Law Number 23 of 2004 concerning the Elimination of Domestic Violence, and the Law on Witness and Victim Protection. The results of the study indicate that, normatively, domestic violence has been comprehensively regulated as a public law issue. In practice, victim protection has not been optimally implemented due to obstacles from law enforcement, community culture, and limited supporting facilities.